CHARACTERISTICS AND VISITING MOTIVES ANALYSIS OF DOMESTIC TOURISTS TO TOURISM DESTINATIONS OF PROVINCE LAMPUNG - M. Ariza Eka Yusendra; Yusminar Wahyuningsih (Prosiding International conference on Information Technology and Business (ICITB), 2016)
Lampung province also one of provinces that put the tourism sector as a development priority. It can be seen from the development priorities of Lampung Province in 2015-2020, one of them is "Developing the tourism industry and creative economy and also to improve the competitiveness of cooperatives and SMEs". The result is the trend number of tourists visiting and spending for the area of Lampung Province has increased from year to year. The Condition of the number of tourists rising to Lampung Province is due to several factors besides influenced by national stability, it is also influenced by expanded marketing and focused initiative programs with the right approach mechanism. These proves that Lampung tourism stakeholders should not be solely dependent on the availability of tourism object, holistic tourism marketing needed to be able to develop "the prestige and the value " a tourism destinations. Characteristics and visiting motives analysis of domestic tourists to tourism destinations is the basis for the development of marketing strategy. If Lampung tourism stakeholders can continuously perform these activities, it will certainly have an impact on the crafting of marketing strategies that can fullfil the needs and desires of tourists who has become customers so that not only increase the number of tourist, but also can improve the satisfaction of tourists who visit and will become loyal.Key Words : tourist characteristics, tourism visiting motives, Lampung Tourism Destinations